Health in the Inca heartland: A paleopathological analysis of burials from the Cuzco region of Peru - Andrushko, Valerie A. (International Journal of Osteoarchaeology, 2021)
While much is known about the rise and expansion of the Inca Empire (AD 1438–1532) throughout the Andean region of South America, the health effects of the empire in its capital region remain unclear. The present study addresses the Inca Empire's impact on health in the Cuzco region of Peru through an analysis of four conditions (dental enamel hypoplasias, cribra orbitalia, porotic hyperostosis and periosteal lesions) in 929 pre-Inca and Inca burials. The study results show little change in health from the Late Intermediate Period (AD 1000–1438) to the Inca Imperial Period (AD 1438–1532). When the location of the Inca burial sites was analysed, individuals from sites closest to the centre of the empire's capital showed lower frequencies in pathological conditions compared with individuals from sites in the countryside. These results suggest that individuals centred in the Inca imperial sphere benefited from their position and experienced better health. A similar finding was also seen with the previous Wari occupation of Cuzco in the Middle Horizon (AD 600–1000), as burials within the Wari imperial sphere exhibited fewer non-specific stress indicators than those outside of it. Overall, the frequencies of pathological conditions in the Cuzco region, which ranged from 4.6% for porotic hyperostosis to 18.8% for periosteal lesions, were lower than frequencies from many coastal Peruvian sites. These differences may relate to a diverse diet provided by the Cuzco region ecosystem, as well as the absence of ecological challenges that affected coastal populations. © 2021 John Wiley & Sons, Ltd.
4 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103956435
Keywords: dept.ant; peer-reviewed